2002
DOI: 10.1152/ajplung.00343.2001
|View full text |Cite
|
Sign up to set email alerts
|

IL-13-dependent autocrine signaling mediates altered responsiveness of IgE-sensitized airway smooth muscle

Abstract: In testing the hypothesis that interleukin-4 receptor alpha-subunit (IL-4R alpha)-coupled signaling mediates altered airway smooth muscle (ASM) responsiveness in the atopic sensitized state, isolated rabbit tracheal ASM segments were passively sensitized with immunoglobulin E (IgE) immune complexes, both in the absence and presence of an IL-4R alpha blocking antibody (anti-IL-4R alpha Ab). Relative to control ASM, IgE-sensitized tissues exhibited enhanced isometric constrictor responses to administered ACh and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
109
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 30 publications
8
109
1
1
Order By: Relevance
“…Both IL-4 and IL-13 can be detected in intestinal smooth muscle during nematode infection (40) and are required, with STAT-6, to induce muscle contractility, a putative host mechanism for parasite expulsion (40,41). Likewise, airway smooth muscle can produce IL-13 and has been linked to an autocrine pathway inducing smooth muscle hypertrophy, a feature of asthma pathophysiology (42). Moreover, a gene array study by Lee et al (43) has highlighted vast numbers of distinctive genes that are switched on following IL-13 treatment of lung epithelial cells, fibroblasts, and smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-4 and IL-13 can be detected in intestinal smooth muscle during nematode infection (40) and are required, with STAT-6, to induce muscle contractility, a putative host mechanism for parasite expulsion (40,41). Likewise, airway smooth muscle can produce IL-13 and has been linked to an autocrine pathway inducing smooth muscle hypertrophy, a feature of asthma pathophysiology (42). Moreover, a gene array study by Lee et al (43) has highlighted vast numbers of distinctive genes that are switched on following IL-13 treatment of lung epithelial cells, fibroblasts, and smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several cell types produce IL-13, including Th2-type cells, mast cells, airway smooth muscle cells, NK cells, and NK T cells; some have been implicated in the development of AHR (41,42,48,49). Although we have shown that CD8 ϩ T cells produce IL-13, it is also possible that CD8 ϩ T cells may not only produce IL-13 but also induce another cell type to release IL-13 for the full development of AHR.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, these processes lead to helper T type 2 (Th2) cell differentiation and further production of the Th2 cytokines IL-4, IL-5, and IL-13 (4-6), and memory T and B cells are generated that can lead to chronic inflammation. Much of the remodeling and dysfunction in resident lung cells that are associated with asthma can be reproduced by IL-13 exposure, including goblet cell metaplasia (7), subepithelial fibrosis (8), and airway hyperresponsiveness (9)(10)(11)(12). IL-4 can mimic many of the effects of IL-13 and is thought particularly important in IgE class switching by B cells.…”
mentioning
confidence: 99%